2023
DOI: 10.1002/asia.202300619
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advancements in Metal‐Organic Framework‐Based Membranes for Hydrogen Separation: A Review

Umair Baig,
Abdul Waheed,
Shehzada Muhammad Sajid Jillani

Abstract: Metal‐organic frameworks (MOFs) are promising porous materials that have huge potential for gas separation when put in the membrane configuration. MOFs have huge potential of the MOFs such as excellent pore size, ease of tuning the pore chemistry, higher surface area, and chemical and thermal stabilities, MOFs have been explored for various gas separation and storage applications. This review discusses various approaches for fabricating MOFs‐based membranes for the separation of H2 gas from a variety of feeds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…MOFs have been found to show many advantages, such as high porosity, tunable architecture, good thermal stability, high specific surface area, and so on, due to which they have been paid much attention in academic societies [ 14 ]. In addition to applications in the fields of adsorption and separation [ 15 ], catalysis [ 16 ], sensing [ 17 ], and energy storage and conversion [ 18 ], MOFs have also been verified to be effective in the area of tribology. Wu et al [ 19 ] have used MOFs@DDP as additives for base oils, and they revealed its good anti-friction and anti-wear effects, which were ascribed to the ball-bearing effect of MOFs in the friction process.…”
Section: Introductionmentioning
confidence: 99%
“…MOFs have been found to show many advantages, such as high porosity, tunable architecture, good thermal stability, high specific surface area, and so on, due to which they have been paid much attention in academic societies [ 14 ]. In addition to applications in the fields of adsorption and separation [ 15 ], catalysis [ 16 ], sensing [ 17 ], and energy storage and conversion [ 18 ], MOFs have also been verified to be effective in the area of tribology. Wu et al [ 19 ] have used MOFs@DDP as additives for base oils, and they revealed its good anti-friction and anti-wear effects, which were ascribed to the ball-bearing effect of MOFs in the friction process.…”
Section: Introductionmentioning
confidence: 99%